Superradiant Emission from Coherent Excitons in van Der Waals Heterostructures. (12th May 2021) - Haider, Golam; Sampathkumar, Krishna; Verhagen, Tim; Nádvorník, Lukáš; Sonia, Farjana J.; Valeš, Václav; Sýkora, Jan; Kapusta, Peter; Němec, Petr; Hof, Martin; Frank, Otakar; Chen, Yang‐Fang; et al.
Abstract: Recent advancements in isolation and stacking of layered van der Waals materials have created an unprecedented paradigm for demonstrating varieties of 2D quantum materials. Rationally designed van der Waals heterostructures composed of monolayer transition‐metal dichalcogenides (TMDs) and few‐layer hBN show several unique optoelectronic features driven by correlations. However, entangled superradiant excitonic species in such systems have not been observed before. In this report, it is demonstrated that strong suppression of phonon population at low temperature results in a formation of a coherent excitonic‐dipoles ensemble in the heterostructure, and the collective oscillation of those dipoles stimulates a robust phase synchronized ultra‐narrow band superradiant emission even at extremely low pumping intensity. Such emitters are in high demand for a multitude of applications, including fundamental research on many‐body correlations and other state‐of‐the‐art technologies. This timely demonstration paves the way for further exploration of ultralow‐threshold quantum‐emitting devices with unmatched design freedom and spectral tunability. Abstract : Excitons in van‐der‐Waals heterostructure composed of monolayer semiconductors separated by few‐layers of hBN turn into an ensemble of aggregated coherent excitons at low temperature due to collective light‐matter interaction under common photon field. The collective oscillation produces a standing wave of oscillating electric‐dipoles that provides optical feedback to a highly phase‐synchronized superradient emission.